Plant oils in sport nutrition: a narrative literature review - Kostrakiewicz-Gieralt, K. (Nutrients, 2025)
Background/Objectives. Edible oils derived from herbaceous and woody plants are an important nutritional resource, assuring the health and performance of sportspeople. The aim of this study was to review the inventions and experimental articles referring to the application of vegetable oils in food products for sportspeople and published in the period of 2015-2024. Methods. The literature search was conducted across Google Scholar, Scopus, and ISI Web of Science databases, as well as by using Google Patents and Espacenet Patent search engines. Results. Altogether, 58 patents and 35 original articles were found. In total, the use of 39 plant taxa belonging to 27 botanical families was documented. The majority of disclosures refer to sports nutrition, post-exercise recovery support, and/or sport performance improvement and may be provided in the form of powders, tablets, beverages, and/or capsules. According to the reviewed studies, the consumption of olive, walnut, and perilla oils beneficially affects the morphological, physiological, and biochemical indicators of sportspeople. The substantial intake of olive oil reported by sportspeople from southern Europe is linked to the recommendations of the Mediterranean diet, while lower consumption of other vegetable oils might be connected to focusing on intake of carbohydrates and/or proteins and/or consumption of other fat sources such as seeds or nuts. Conclusions. Considering the great potential of useful plant species, it might be concluded that future investigations should focus on both (i) further investigations of the effects of well-known vegetable oils on the health and performance of sportspeople, and (ii) searching for novel plant oil sources, suitable for the preparation of food products dedicated to amateur and professional sportspeople.